How Clinical Decision Tasks Modulate Emotional Related Eeg Responses in Nursing Students - Garcia-Serrano, A (Taylor and Francis Ltd., 2024)
Healthcare professionals play a vital role in conveying sensitive information as patients undergo stressful, demanding situations. However, the underlying neurocognitive dynamics in routine clinical tasks remain underexplored, creating gaps in healthcare research and social cognition models. Here, we examined whether the type of clinical task may differentially affect the emotional processing of nursing students in response to the emotional reactions of patients. In a within-subjects design, 40 nursing students read clinical cases prompting them to make procedural decisions or to respond to a patient with a proper communicative decision. Afterward, participants read sentences about patients’ emotional states; some semantically consistent and others inconsistent along with filler sentences. EEG recordings toward critical words (emotional stimuli) were used to capture ERP indices of emotional salience (EPN), attentional engagement (LPP) and semantic integration (N400). Results showed that the procedural decision task elicited larger EPN amplitudes, reflecting pre-attentive categorization of emotional stimuli. The communicative decision task elicited larger LPP components associated with later elaborative processing. Additionally, the classical N400 effect elicited by semantically inconsistent sentences was found. The psychophysiological measures were tied by self-report measures indexing the difficulty of the task. These results suggest that the requirements of clinical tasks modulate emotional-related EEG responses. © 2024 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Healthcare professionals; EEG; processing emotional information; emotional regulation strategies